Hemodynamic Response Alterations in Sensorimotor Areas as a Function of Barbell Load Levels during Squatting: An fNIRS Study - Kenville, Rouven; Maudrich, Tom; Carius, Daniel; Ragert, Patrick (Frontiers in Human Neuroscience, 2017)
Functional near – infrared spectroscopy (fNIRS) serves as a promising tool to examine hemodynamic response alterations in a sports-scientific context. The present study aimed to investigate how brain activity within the human motor system changes its processing in dependency of different barbell load conditions while executing a barbell squat (BS). Additionally, we used different fNIRS probe configurations to identify and subsequently eliminate potential exercise induced systemic confounders such as increases in extracerebral blood flow. Ten healthy, male participants were enrolled in a cross-over design. Participants performed a barbell squat task with random barbell load levels [0% 1 RM (one repetition maximum), 20% 1 RM & 40% 1 RM for a barbell squat] during fNIRS recordings. Initially, we observed global hemodynamic response alterations within and outside the human motor system. However, short distance channel regression of fNIRS data revealed a focalized hemodynamic response alteration within bilateral SPL (superior parietal lobe) for oxygenated hemoglobin (HbO2) and not for deoxygenated hemoglobin (HHb) when comparing different load levels. These findings indicate that the previously observed load/ force - brain relationship for simple and isolated movements is also present in complex multi-joint movements such as the BS. Altogether, our results show the feasibility of fNIRS to investigate brain processing in a sports-related context. We suggest for future studies to incorporate short distance channel regression of fNIRS data to reduce the likelihood of false-positive hemodynamic response alterations during complex whole body movements.